Do Helicobacter pylori therapeutic vaccines need to be tailored to the age of the recipient?. (April 2012) - Sutton, Philip; Robinson, Karen
Helicobacter pylori infections typically commence during childhood and last for life. Freire de Melo and colleagues compared cytokine profiles in the stomachs of H. pylori -infected and H. pylori -uninfected children and adults from Brazil. They suggest that the immune effector response in infected children differs from infected adults, specifically that stomachs of infected children contained elevated regulatory T-cell markers and less IL-17 compared with adults. As vaccine-mediated protection against H. pylori is believed to involve IL-17 and to be inhibited by regulatory T cells, this raises the possibility that individual H. pylori vaccines may have different efficacies in children and adults.